Short Sleep Duration, Obstructive Sleep Apnea, Shiftwork, and the Risk of Adverse Cardiovascular Events in Patients After an Acute Coronary Syndrome. Issue 10 (10th October 2017) - Barger, Laura K.; Rajaratnam, Shantha M.W.; Cannon, Christopher P.; Lukas, Mary Ann; Im, KyungAh; Goodrich, Erica L.; Czeisler, Charles A.; O'Donoghue, Michelle L.
Abstract : Background: It is unknown whether short sleep duration, obstructive sleep apnea, and overnight shift work are associated with the risk of recurrent cardiovascular events in patients after an acute coronary syndrome. Methods and Results: SOLID‐TIMI 52 (The Stabilization of PLaques UsIng Darapladib‐Thrombolysis in Myocardial Infarction 52 Trial) was a multinational, double‐blind, placebo‐controlled trial that enrolled 13 026 patients ≤30 days of acute coronary syndrome. At baseline, all patients were to complete the Berlin questionnaire to assess risk of obstructive sleep apnea and a sleep and shift work survey. Median follow‐up was 2.5 years. The primary outcome was major coronary events (MCE; coronary heart disease death, myocardial infarction, or urgent revascularization). Cox models were adjusted for clinical predictors. Patients who reported <6 hours sleep per night had a 29% higher risk of MCE (adjusted hazard ratio, 1.29; 95% confidence interval, 1.12–1.49; P <0.001) compared with those with longer sleep. Patients who screened positive for obstructive sleep apnea had a 12% higher risk of MCE (1.12; 1.00–1.24; P =0.04) than those who did not screen positive. Overnight shift work (≥3 night shifts/week for ≥1 year) was associated with a 15% higher risk of MCE (1.15; 1.03–1.29; P =0.01). A step‐wise increase in cardiovascular risk was observed for individuals with more than 1 sleep‐related risk factor. Individuals with all 3 sleep‐related risk factors had a 2‐fold higher risk of MCE (2.01; 1.49–2.71; P <0.0001). Conclusions: Short sleep duration, obstructive sleep apnea, and overnight shift work are under‐recognized as predictors of adverse outcomes after acute coronary syndrome. Increased efforts should be made to identify, treat, and educate patients about the importance of sleep for the potential prevention of cardiovascular events. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01000727.